2021
DOI: 10.1155/2021/9332848
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Effect Analysis of Plasma Bipolar Intelligent Electrotonic for Cystostomy in the Treatment of Senile Prostatic Hyperplasia

Abstract: To solve prostatic hyperplasia in the elderly, a method of cystostomy with plasma bipolar resection was proposed. From January 2019 to March 2020, 42 patients with BPH who needed surgical treatment in the urological department were selected. Cystostomy was performed in bipolar TURP. The cystostomy group and robot group were divided into two groups. The surgical safety, surgical efficiency, complications, and nursing time between the two groups were compared. The results showed that the experimental and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%